Analysis of uniform illumination system with imperfect Lambertian LEDs - Tan, Jiajie; Yang, Kecheng; Xia, Min; Yang, Ying (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
This paper offers a novel algorithm to better design LEDs arrays for illumination systems. First, the illuminance distribution of LED arrays is studied through theoretical analysis. Second, we present the algorithm criterion and steps. And finally, we use computer to simulate and verify this method. The results show that the illumination uniformity is significantly affected by the spacing of each light in the LED array. The analysis method presented here in this thesis can be usefully applied in LED in the illumination engineering.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 507-517
Keywords: optyka; light emitting diode; uniform illumination; imperfect Lambertian distribution